THE INFLUENCE OF TRANSLATION STUDIES ON MODERN PHILOLOGICAL RESEARCH - Rasulova Diyora Ziyodulla qizi; Abduramanova Diana Valerevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Translation studies has become a transformative discipline, crossing linguistic, cultural, and historical divides. This article explores how translation studies have reshaped modern philology, introducing interdisciplinary methodologies that enrich textual analysis and comparative research. Examining case studies of literary, historical, and sacred texts, this study highlights the integration of translation theories into philological practices, such as the analysis of meaning shifts, textual fidelity, and cultural mediation. She argues that translation studies not only complement traditional philological methods, but also broaden the scope of the field, fostering a more comprehensive understanding of world literatures and their interrelated histories. This research highlights the need for translation as a tool and as a perspective for modern philological research, opening the way to innovative perspectives on the transmission and reception of texts.